Pendekatan Neorealis terhadap Studi Keamanan Nasional - Suryanti, Budhi Tri (Universitas Perrtahanan Indonesia (UNHAN), 2021)
Neo-realist approach towards national security is still applicable even until now. The current changes in strategic environment of the world has just made living as a state even more complex. The ever-changing situation is growing rapidly, and the a certain strategic approaches is needed to fully grasp and deal with the situation. This article aims to describe the neoreailsm approach towards the study of national security. Content analysis method will be used in this article. According to Kenneth Waltz, power is the most important factor in international relations. The competition between states is just a product of the current structure of international system. From more than 20 articles referenced here, it can be summarized that changes in strategic environment is heavily affected by the latest industrial revolution. Thus, from neorealist approach, the security dilemma is even bigger than it was decades ago. New threats and opportunites come together and raised the bar even higher in modern times.Keywords: Neo-realism, National Security, security dilemma